Body composition in patients with early rheumatoid arthritis - Yu. N. Gorbunova; L. V. Kondratyeva; T. V. Popkova; N. V. Demin; A. V. Smirnov; E. L. Nasonov (Научно-практическая ревматология)
Aim of the study was to clarify the body composition in patients with early rheumatoid arthritis before starting therapy with synthetic basic anti-inflammatory drugs, genetically engineered biological drugs and glucocorticoids using dual-energy X-ray absorptiometry and to assess the effect of inflammation and metabolic syndrome on body composition.Material and methods. The study included 37 patients (31 women and 6 men) with early rheumatoid arthritis. The control group consisted of 19 healthy donors without rheumatic diseases. Patients with rheumatoid arthritis and the control group were measured by waist size, height and weight, and body mass index was calculated. Body composition was determined by means of dual-energy X-ray absorptiometry using the “Whole Body” program on the HOLOGIC device (USA). The presence of metabolic syndrome was assessed according to the criteria of the International Diabetes Federation (IDF).Results. Patients with early rheumatoid arthritis had less lean tissue mass, which was negatively correlated with inflammatory markers (ESR and C-reactive protein levels). Overweight and obesity were diagnosed in 24% and 27% of patients with early rheumatoid arthritis, respectively. Patients with rheumatoid arthritis and metabolic syndrome had a higher body weight, body mass index, waist size, and adipose tissue mass than patients without metabolic syndrome. With the help of instrumental methods, it is shown that in rheumatoid arthritis there is a redistribution of fat mass in the body, its predominant accumulation in the trunk area and a parallel decrease in the volume of muscle tissue.Conclusion. Rheumatoid inflammation and metabolic syndrome affect body composition of patients with early rheumatoid arthritis before the start of antirheumatic therapy.